Laud Humphreys : prophet of homosexuality and sociology - Galliher, John F.; Brekhus, Wayne; Keys, David P. (University of Wisconsin Press, 2004)
Laud Humphreys (19301988) was a pioneering and fearless sociologist, an Episcopal priest, and a civil rights, gay, and antiwar activist. This biography examines the groundbreaking work through the life of a complex man, and the life of the man through his controversial work.